Syringin exhibits anticancer effects in HeLa human cervical cancer cells by inducing apoptosis, cell cycle arrest and inhibition of cell migration (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed at to demonstrate the antitumor effects of syringin in HeLa human cervical cancer cells. Its effects on apoptosis, cell cycle phase distribution as well as on cell migration were also examined. The effect on cell proliferation was evaluated by MTT assay, while as effects on colony formation were assessed using clonogenic assay. Syringin inhibited cancer cell growth in HeLa cells in a time-dependent as well as in a concentration-dependent manner. Syringin also led to inhibition of colony formation efficacy with complete suppression at 100 µM drug dose. Syringin could induce G2/M cell cycle arrest along with slight sub-G1 cell cycle arrest. HeLa cells began to emit red fluorescence as the dose of syringin increased from 0 µM in vehicle control to 100 µM. Syringin also inhibited cell migration in a dose-dependent manner with 100 µM dose of syringin leading to 100% inhibition of cell migration.Video Clip of Methodology:Clonogenic assay: 4 min 21 sec   Full Screen   Alternative